Moesin Is a Novel Biomarker of Endothelial Injury in Sepsis - Yikun Chen; Jiajia Wang; Lei Zhang; Jianjie Zhu; Yuanyuan Zeng; Jian-an Huang (Journal of Immunology Research)
Objective. Increased vascular permeability and inflammation are principal hallmark of sepsis. Moesin (MSN) is a membrane-associated cytoskeleton protein and crucial for the vascular endothelial function. This study is aimed at evaluating the role of MSN in endothelial injury during the process of sepsis. Methods. Serum MSN in septic patients was measured by ELISA. BALB/c mice were injected with different doses of lipopolysaccharide (LPS) or underwent cecal ligation and single or double puncture (CLP) to mimic sublethal and lethal sepsis. After treatment, their serum MSN and PCT levels, wet to dry lung weights (W/D ratio), bronchoalveolar lavage fluid (BALF) protein concentrations, and lung injury scores were measured. The impact of MSN silencing on LPS-altered Rock1/myosin light chain (MLC), NF-κB, and inflammatory factors in human microvascular endothelial cells (HMECs), as well as monolayer HMEC permeability, was tested in vitro. Results. Compared with healthy controls, serum MSN increased in septic patients and was positively correlated with SOFA scores and serum PCT levels in septic patients. LPS injection significantly increased serum the MSN and PCT expression, BALF protein levels, and W/D ratio, and the serum MSN levels were positively correlated with serum PCT, lung W/D ratio, and lung injury scores in mice. Similar results were obtained in the way of CLP modelling. LPS enhanced MSN, MLC, NF-κB phosphorylation, increased Rock1 expression, and inflammatory factors release in the cultured HMECs, while MSN silencing significantly mitigated the LPS-induced Rock1 and inflammatory factor expression, NF-κB, and MLC phosphorylation as well as the monolayer hyperpermeability in HMECs. Conclusions. Increased serum MSN contributes to the sepsis-related endothelium damages by activating the Rock1/MLC and NF-κB signaling and may be a potential biomarker for evaluating the severity of sepsis.